2016
DOI: 10.1074/jbc.r115.713313
|View full text |Cite
|
Sign up to set email alerts
|

The β-Arrestins: Multifunctional Regulators of G Protein-coupled Receptors

Abstract: The ␤-arrestins (␤arrs) are versatile, multifunctional adapter proteins that are best known for their ability to desensitize G protein-coupled receptors (GPCRs), but also regulate a diverse array of cellular functions. To signal in such a complex fashion, ␤arrs adopt multiple conformations and are regulated at multiple levels to differentially activate downstream pathways. Recent structural studies have demonstrated that ␤arrs have a conserved structure and activation mechanism, with plasticity of their struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
227
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(229 citation statements)
references
References 101 publications
2
227
0
Order By: Relevance
“…β-arrestins belongs to the family of arrestin, the classical functions of β-arrestins are involved in the desensitization and recycling of G protein-coupled receptors (Smith and Rajagopal, 2016), while increasingly researchers suggested that β-arrestins also can to modulate intracellular functions, for example, Sun et al found that β-arrestin2 was involved in the proliferation of hepatic stellate cells via ERK pathway (Sun et al, 2013), while Li et al suggested that β-arrestin1 attenuate arthritis through impairing the differentiation of TH17 cell . β-arrestin1 was one member of β-arrestins, and functioned as multiprotein scaffolds in diverse cellular processes to modulate complex regulating pathways, such as cell proliferation and migration, as well as inflammatory reaction (Talbot et al, 2012;Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…β-arrestins belongs to the family of arrestin, the classical functions of β-arrestins are involved in the desensitization and recycling of G protein-coupled receptors (Smith and Rajagopal, 2016), while increasingly researchers suggested that β-arrestins also can to modulate intracellular functions, for example, Sun et al found that β-arrestin2 was involved in the proliferation of hepatic stellate cells via ERK pathway (Sun et al, 2013), while Li et al suggested that β-arrestin1 attenuate arthritis through impairing the differentiation of TH17 cell . β-arrestin1 was one member of β-arrestins, and functioned as multiprotein scaffolds in diverse cellular processes to modulate complex regulating pathways, such as cell proliferation and migration, as well as inflammatory reaction (Talbot et al, 2012;Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…GPCR kinases (GRK) and β-arrestin proteins are important in the post-activation behavior of GPCRs (Claing et al, 2002; Smith and Rajagopal, 2016). GRKs phosphorylate agonist activated GPCR.…”
Section: Introductionmentioning
confidence: 99%
“…There are two b-arr isoforms, b-arr-1 and b-arr-2, and they share approximately 80% sequence identity [2]. It is now clearly established that these b-arrs are capable of interacting with distinct signaling partners, thereby regulating a variety of downstream pathways of GPCRs [3]. Notably, some agonists can selectively mediate signaling through b-arrs (b-arr-biased signaling) while blocking signaling through G proteins (G protein-biased signaling) [4e6].…”
Section: Introductionmentioning
confidence: 99%